BASIC DIFFICULTIES AND SOLUTIONS IN LEARNING A NEW LANGUAGE - Mustayeva, Guldora (Журнал иностранных языков и лингвистики, 2023)
Our article will consider most of the difficulties of learning a foreign language and will teach you how to gradually expand the material of a foreign language that we are faced with.